Shedding light on pediatric diseases: multispectral optoacoustic tomography at the doorway to clinical applications. - Regensburger, Adrian; Wagner, Alexandra; Claussen, Jing; Waldner, Maximilian; Knieling, Ferdinand (Molecular and Cellular Pediatrics, 2020)
Optoacoustic imaging (OAI), or photoacoustic imaging (PAI), has fundamentally influenced basic science by providing high-resolution visualization of biological mechanisms. With the introduction of multispectral optoacoustic tomography (MSOT), these technologies have now moved closer to clinical applications. MSOT utilizes short-pulsed near-infrared laser light to induce thermoelastic expansion in targeted tissues. This results in acoustic pressure waves, which are used to resolve specific endo- and exogenous chromophores. Especially in the pediatric population, this non-invasive imaging approach might hold fundamental advantages compared to conventional cross-sectional imaging modalities. As this technology allows the visualization of quantitative molecular tissue composition at high spatial resolution non-invasively in sufficient penetration depth, it paves the way to personalized medicine in pediatric diseases.
EVALuna2:383218